Role of Mycorrhiza in Maintaining Carbon Stocks in Disturbed and Undisturbed Ecosystems of Central Himalayan region - Nautiyal, Prachi; Pokhriya, Priya; Melkania, Uma; Arunachalam, K.; Arunachalam, A. (Indian Journal of Hill Farming, 2017)
Carbon management is one of the most relevant issues among the environmentalists, today. A viable option for reducing atmospheric CO2 may be carbon sequestration by agricultural and forested regions. Forest ecosystems represent 60% of the terrestrial carbon budget, which suggests that forest management and forest disturbances may have a profound effect on carbon cycling. Mycorrhiza contributes to many soil characteristics such as organic carbon content, carbon sequestration, retention of moisture and thus, somehow, affects the climatic pattern. It receives 10 to 20% of the carbon fixed by its host plant. As such, it could potentially sequester a significant amount of carbon in ecosystems. An integrated study to assess the carbon stock in the soil has been conducted in the pine and oak forests of the central Himalayan region of Nainital hills and was compared with that of the agricultural soil with emphasis on mycorrhiza. It was found that the value for carbon stock was highest (4.84g/cm3) in oak soil where the mycorrhizal spore count was greater. Lowest stock (2.21g/cm3) in agricultural soil also corresponded with poor spore count.